Odpowiedzi

2009-09-15T15:53:25+02:00
Najpierw pomnozymy wszystko razy 60 w celu pozbycia się ułamków
a więc
40-15+90x=30-50x+30-36
'x' na jedną stronę reszta na drugą
140x=60-36-25
140x=-1
x=-1/140
spr:
2/3-(1-6x)/4=½-(5x-3)/6-⅗ /•60
40-15+90x=30-50x+30-36
140x=-1
140•-1/140=-1
-1=-1 ok
  • Użytkownik Zadane
2009-09-15T16:53:42+02:00
⅔-(1-6x)/4 = ½- (5x-3)/6-0,6 /*60
40-15+90x=30-50x+30-36
140x=60-36-25
140x=-1
x=-1/140
sprawdzenie:

2/3-(1-6x)/4=½-(5x-3)/6-⅗ /*60
40-15+90x=30-50x+30-36
140x=-1
140*-1/140=-1
-1=-1
L=P => x=-1/140